Las estrategias metodológicas propuestas en la actualización y fortalecimiento curricular para la enseñanza de las ciencias naturales y el desarrollo de destrezas con criterios de desempeño en los estudiantes de educación general básica del colegio nacional nocturno doctor Benjamín Carrión de la ciudad de Loja. Periodo 2012- 2013. Lineamientos alternativos - Ramírez Jiménez, Rosa Karina (2014)
Education has seen the need to raise a number of changes to improve quality in the training of young people, which is why, in recent years there have been new methodological strategies to help teaching and develop skills with performance criteria considering that the approaches are resources that the teacher uses in daily teaching, the same that promote skill development with performance criteria. This thesis is based on the theoretical and empirical information collected in relation to the variables proposed in the following topic: Methodological strategies proposed to update and strengthen Curriculum for teaching natural science and skills development with performance criteria students of General Basic Education National college Night Doctor Benjamin Carrión de Loja. Period 2012-2013 Alternative Guidelines. Analyze the proposed methodological strategies to update and strengthen Curriculum for Science teaching and the development of skills with Performance Criteria in students: variables with the overall aim of the theme is expressed as follows arose General Basic Education National College Night Doctor Benjamin Carrion in the city of Loja. Necessary methods were applied to obtain such information such as bibliographic Description method, Analytic-synthetic method, scientific method, statistical and allowed obtaining important data on the research process. According to the research it became known that the approaches raised in the Updating and Strengthening Curriculum basic general education, not used properly teachers for teaching natural science but prioritize methodological strategies such as: concept maps, summaries, transcripts guidebook and dictation. It was also determined that the incorrect application of the methodology for teaching strategies does not contribute to the development of skills with performance criteria students in the subject of Science generating traditional teaching where students only transcribed texts or perform repetitive activities producing fatigue and lack of student interest in the subject.